Extreme mid-winter drought weakens tree hydraulic–carbohydrate systems and slows growth - Earles, J. Mason; Stevens, Jens T.; Sperling, Or; Orozco, Jessica; North, Malcolm P.; Zwieniecki, Maciej A. (The New phytologist, 2018)
Rising temperatures and extended periods of drought compromise tree hydraulic and carbohydrate systems, threatening forest health globally. Despite winter’s biological significance to many forests, the effects of warmer and dryer winters on tree hydraulic and carbohydrate status have largely been overlooked. Here we report a sharp and previously unknown decline in stem water content of three conifer species during California’s anomalous 2015 mid-winter drought that was followed by dampened spring starch accumulation. Recent precipitation and seasonal vapor pressure deficit (VPD) anomaly, not absolute VPD, best predicted the hydraulic patterns observed. By linking relative water content and hydraulic conductivity (K h), we estimated that stand-level K h declined by 52% during California’s 2015 mid-winter drought, followed by a 50% reduction in spring starch accumulation. Further examination of tree increment records indicated a concurrent decline of growth with rising mid-winter, but not summer, VPD anomaly. Thus, our findings suggest a seasonality to tree hydraulic and carbohydrate declines, with consequences for annual growth rates, raising novel physiological and ecological questions about how rising winter temperatures will affect forest vitality as climate changes.